الدور الوسيط للتحكم الذاتي في العلاقة بين وسائل التواصل الاجتماعي والهوية الوطنية لدى طلبة الجامعات في سلطنة عمان في ضوء رؤية عمان : The Mediating Role off Self-Control in the Relationship Between Social Media and National Identity Among University Students in the Sultanate of Oman in Light of Oman Vision 2040 - Said Shdhani, Zubaida Salim; Mohamed Adnan, Mohamad Azrien; Aldhafri, Said (Al-Basirah Journal, 2025)
This study examines the impact of social media on youth in the Sultanate of Oman, highlighting the high level of engagement among this group on digital platforms and the negative and positive aspects of their use. The article explores how certain groups exploit these platforms to spread deviant ideas, negatively impacting youth values ​​and morals. The study indicates that excessive use of social media can lead to negative emotions such as depression and anxiety, particularly due to exposure to negative content and misleading news. While this use enhances learning and communication capabilities, it raises concerns about the erosion of authentic social bonds and increased isolation. The study also highlights the importance of enhancing cultural awareness and critical thinking skills among youth to help them distinguish between good and bad content. The questions addressed the level of self-control, national identity, and social media use among university students in the Sultanate of Oman, in the context of Oman Vision 2040. These questions aim to explore the relationship between these various factors, helping to understand how social media can impact national identity and self-control among Omani youth. One of the most important findings of this study is that it highlights the importance of viewing national identity as a critical issue that requires a comprehensive understanding of the multiple factors that influence it. Although not the decisive mediator in this relationship, self-control remains an important element in promoting positive use of social media. By developing self-control skills among young people, national identity can be strengthened and their role in society can be activated.